The identification of new roles for nicotinamide mononucleotide after spinal cord injury in mice: an RNA-seq and global gene expression study - Zhang, Chunjia; Li, Yan; Bai, Fan; Talifu, Zuliyaer; Ke, Han; Xu, Xin; Li, Zehui; Liu, Wubo; Pan, Yunzhu; Gao, Feng; Yang, Degang; Wang, Xiaoxin; et al. (Frontiers in Cellular Neuroscience, 2023)
Nicotinamide mononucleotide (NMN) serves as an important precursor to nicotinamide adenine dinucleotide (NAD+) and has been shown to provide neuroprotective effects in neurological diseases. In this study, a moderate-to-severe spinal cord injury (SCI) model was established in mice, and NMN treatment was administered immediately after injury for seven consecutive days. NMN supplementation restored NAD+ levels after SCI, promoted motor function recovery, and alleviated pain. This could potentially be associated with alterations in NAD+ dependent enzyme levels. RNA sequencing (RNA-seq) revealed that NMN can inhibit inflammation and potentially regulate signaling pathways, including interleukin-17 (IL-17), tumor necrosis factor (TNF), tolllike receptor, nod-like receptor, and chemokine signaling pathways. In addition, the construction of a protein-protein interaction (PPI) network and the screening of core genes showed that interleukin 1β (IL-1β), interferon regulatory factor 7 (IRF 7), C-X-C motif chemokine ligand 10 (Cxcl10), and other inflammation-related factors, changed significantly after NMN treatment. qRT-PCR confirmed the inhibitory effect of NMN on inflammatory factors (IL-1β, TNF-α, IL-17A, IRF7) and chemokines (chemokine ligand 3, Cxcl10) in mice following SCI. Our findings suggest that supplementation of NMN after SCI may be a potential strategy to improve inflammation response, alleviate pain, and restore motor function.